The effect of intravenous lidocaine on propofol dosage in painless bronchoscopy of patients with COPD - Yang, Li; He, Tao; Liu, Min-Xiao; Han, Shi-Qiang; Wu, Zhi-Ang; Hao, Wei; Lu, Zhi-Xia (Frontiers in Surgery, 2022)
Background: We tested the hypothesis that i.v. lidocaine reduces propofol requirements in painless bronchoscopy in patients with COPD. Methods: 93 patients undergoing bronchoscopy were included in this randomized placebo-controlled study. The patients were randomly divided into two groups. After the intravenous doses of nalbuphine, patients were given a bolus of propofol, titrated if necessary until loss of consciousness. Then patients were given i.v. lidocaine (2 mg/kg then 4 mg/kg/h) or the same volume of saline. The primary endpoint was propofol requirements. Secondary endpoints were: the incidence of hypoxemia, incidence of cough during glottis examination, Systolic blood pressure (SBP) and heart rate (HR) during bronchoscopy procedures, the bronchoscopist’s comforts, time for wakefulness before recovery. Results: Lidocaine infusion resulted in a significant reduction in propofol requirements (p < 0.0001), the incidence of hypoxemia (p = 0.001) and cough (p = 0.003) during examination decreased significantly in lidocaine group. During the examination, the fluctuation of SBP and HR was significantly lower than that in the control group, and the difference was statistically significant (p < 0.05). Bronchoscopist’s comforts were higher in lidocaine group (p < 0.001), and time for wakefulness (p < 0.001) were significantly lower in lidocaine group. Conclusions: In painless bronchoscopy in patients with COPD, intravenous infusion of lidocaine resulted in a reduction in propofol dose requirements and reduce the incidence of adverse events.